Assessing the Food Safety Knowledge of Food Handlers of the Ghana School Feeding Programme in Tamale Metropolis, Ghana - Malik, Bawah Abdul (2018)
A thesis Submitted to the Department of Food Science and Technology, College of Science, in partial fulfilment of the requirements for the degree of Master of Science in Food Quality Management.